1-Methylcyclopropene maintains postharvest quality and extends shelf life of cauliflower - Su Yan; Pufan Zheng; Xiangning Chen; Cunkun Chen; Hongru Zhang; Xingwei Yao; Liya Liang; Tong Li; Liying Ma; Na Zhang; Xiaoxue Li (Postharvest Biology and Technology, 2027)

A novel sandwich immunoassay for Staphylococcus aureus using horseradish peroxidase-conjugated trivalent nanobody - Na Su; Chunxu Yang; Lei Zhu; Heyang Song; Tuyatsetseg Jambal; Li Yi; Rimutu Ji (Food Chemistry, 2026)

High abundance of small-sized microplastics in transport ship domestic sewage: Characteristics and potential ecological risks - Qing Su; Yuxia Li; Lingna Kong; Na Lu; Ling Qu; Yuyang Sun; Xiaodan Zhang; Xiaomeng Wang (Regional Studies in Marine Science, 2026)

Deciphering drought resistance in tetraploid Passiflora edulis by integrated transcriptomic and metabolomic profiling - Xin Su; Chiyu Zhou; Sunling Li; Jianzhen Liao; Xiaoyue Zhang; Na Li; Xuesha Gu; Nianhui Cai; Yulan Xu (Food Bioscience, 2026)

Efficacy and Mechanisms of Combined Central-Peripheral Magnetic Stimulation on Prefrontal-Sensorimotor Cortex Connectivity in Post-Stroke Dysphagia after Supratentorial Stroke: A Randomized, Single-Blind, Parallel-Controlled Trial - Zirui Luo; Zhiying Zhu; Yujue Wang; Na Su; Yajing Xue; Wanqi Zhang; Wei Liao; Yaoyao You; Lin Ling; Mei Li; Junjie Liang; Zulin Dou; et al. (Translational Stroke Research, 2026)

Co-precipitated protein prepared by soybean protein and phycocyanin: Focus on protein structure and nutritional characteristics - Na Sun; Zhe Wang; Jianan Li; Lanxin Li; Shi Liu; Jianling Feng; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Chemistry, 2026)

Daily mortality prediction under compound environmental stressors: Comparing epidemiological time series models and machine learning models - Wanjie Wang; Xiaoyan Zhou; Na Li; Feng Chen; Jingqiao Fu; Zhiyang Su; Yuqing Yao; Xiaoyan Yuan; Sirui Lin; Mengfan Chen; Maji Gan; Jieming Zhong; et al. (Environmental Research, 2026)

Time and pH regulation of the morphology and structure evolution of soybean protein fibrils: Focusing on foaming mechanism and application - Jianan Li; Zhe Wang; Bowen Yang; Xinhui Peng; Shi Liu; Na Sun; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

Nigrospora aurantiaca causes leaf spot disease in Bletilla striata in China - Na Wu; Zhen Su; Junyi Gao; Dengquan Liu; Maoxian Wang; Zhongshun Cai; Cheng Li (Crop Protection, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

miR-133b-3p Mitigates D-Galactose-Induced Hippocampal Neuron Aging Through Autophagy Regulation via the MAPK/ERK Signaling Pathway - Yang Cao; Chen Zhao; Jiaxin Li; Qiang Gao; Chunmei Lv; Jiao Wang; Na Qiang; Wenwen Zhang; Huiyu Su; Xinyu Min; Jinfeng Liu; Xiaoqi Dai; et al. (Molecular Neurobiology, 2026)

Resveratrol Attenuates H2O2-induced Aging and Apoptosis in Mouse Hippocampal Neuron HT22 Cells by Activating Autophagy via the SIRT1/FoxO1 Signaling Pathway - Minghui Cai; Qi Guo; Jiaxin Li; Xiaoqi Dai; Huiyu Su; Wenwen Zhang; Na Qiang; Geng Li; Zihan Jin; Hui Zhu (Molecular Neurobiology, 2026)

The single nucleotide polymorphism rs155787 on the autophagy gene of SQSTM1 is associated with silicosis susceptibility: A multi-stage study - Lijing Jiang; Fan Wang; Mingwei Huai; Wendi Zhang; Xiaofeng Chen; Chunping Li; Xinsheng Zhang; Bingchen Liu; Yao Su; Minjie Chu; Na Sun; Jiandong Jiao; et al. (Toxicology Letters, 2025)

Major vault protein inhibits CSFV replication by promoting cell apoptosis - Bihao Luo; Na Su; Yuehan Quan; Ning Li; Chen Chen; Liang Zhang; Lei Xu; Kangkang Guo (Veterinary Microbiology, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Preparation and Optimization of Pramipexole Hydrochloride Solid Dispersions to Improve Drug Release and Bioavailability - Yuanyuan Ding; Zhenkun Su; Guodong Liang; Na Sai; Xin Wu; Jianping Chen; Yuheng Ma; Ruijuan Li (AAPS PharmSciTech, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Breaking through the bottleneck of nitrogen pollution control in micropolluted water sources: Enhancement of aerobic denitrification efficacy driven by microbial community enrichment and its sustainable application - Honghong Guo; Yuhang Su; Shuhong Xue; Na Li; Rong Li; Sen Wang; Jianwei Bu; Haihan Zhang; Tinglin Huang (Water Research, 2025)

Microplastics and human health: Exposure pathways, toxicity mechanisms, and future research challenges - Zhi Wang; Nuo Li; Yongcheng Ding; Na Li; Menghan Su; Congcong Zhang; Yiqun Li; Qing Wang; Chenyan Sha; Bing Xia; Jie Cheng; Guan Jiang (Journal of Environmental Chemical Engineering, 2025)

Engineered apoferritin-coumarin nanosensor for hyper-sensitive in vivo tracking of plant isoprene emissions - Xuejia Sun; Tingxi Han; Jiaxing Li; Qijun Sun; Chenglin Su; Shuang Cao; Boyuan Qiao; Jiating Xu; Na Niu; Ligang Chen (Chemical Engineering Journal, 2025)

Mitochondrial energy reprogramming via dECM/GP@EVs@Gpnmb to prevent post-myocardial infarction heart failure - Na Li; Ying Wang; Ling Yuan; Shuang Peng; Zhansheng Hu; Baoquan Wang; Dan Zhang; Longxiang Su; Huiping Wu (Chemical Engineering Journal, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

PM2.5 from biofuel smoke induces inflammatory response through the TRPC6/Ca2+/NLRP3 signaling pathway - Yan Chen; Na Zhan; Jinhuang Xu; Yupeng Huang; Yuying Su; Zhongqin Liu; Haisheng Feng; Wenxin Ji; Jiahao Liang; Shenting Zhao; Jianhua Li (Environmental Geochemistry and Health, 2025)

Spatial distribution analysis of secondary metabolites in bolted and unbolted Saposhnikovia divaricata by atmospheric pressure laser ablation carbon fiber ionization mass spectrometry imaging - Na Li; Xialian Cui; Yingjie Lu; Fang Zhang; Su Guo; Yue Su; Yinlong Guo (Analytica Chimica Acta, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Development of corn straw lignin-based cling films for enhanced preservation of strawberries - Tao Yu; Tong Wang; Renguo Zhang; Chenglin Su; Shuang Cao; Yini Zhao; Hejing Wang; Jiaxing Li; Na Niu; Ligang Chen (Food Packaging and Shelf Life, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Effects of homogenization and heat treatment on camel milk: Physicochemical properties, microstructure, and digestibility in infants - Na Su; Li Yi; Naihui Wang; Jing He; Liang Ming; Rendalai Si; Jiayu Zhang; Rimutu Ji (International Dairy Journal, 2025)

Subgrade cumulative deformation probabilistic prediction method based on machine learning - Zhixing Deng; Linrong Xu; Yongwei Li; Yunhao Chen; Na Su; Yuanxingzi He (Soil Dynamics and Earthquake Engineering, 2025)

Optimizing membrane dehumidification performance: A comprehensive review of materials, modules and system - Yilin Liu; Junbao Fan; Jincai Su; Na Li; Xin Cui; Liwen Jin (Journal of Environmental Chemical Engineering, 2025)

Identification and validation of a major QTL, QFhb-6AL, for Fusarium head blight resistance on chromosome 6AL in wheat - Zhenzhen Zhu; Xuecheng Zhu; Na Zhang; Wenxi Wang; Jilu Liu; Fuping Zhang; Xiaomeng Ren; Yanpeng Ding; Fangyao Sun; Xi He; Sijia Hu; Xiuhua Li; et al. (Theoretical and Applied Genetics, 2025)

Deciphering the antibiotic resistome in stratified source water reservoirs in China: Distribution, risk, and ecological drive - Honghong Guo; Rong Li; Yuhang Su; Shuhong Xue; Na Li; Fan Chen; Xuanzi Zhangsun; Haihan Zhang; Xiaoyan Liu; Tinglin Huang (Journal of Hazardous Materials, 2025)

A framework for the construction of effective landscape ecological network with integrating hydrological connectivity: A case study in Dongjiang River Basin, China - Xin Jiang; Zhi-Yun Jiang; Zhen-Ya Li; Jie Su; Li-Na Tang; Meng-Di Wu; Yi-Jia Wang (Journal of Environmental Management, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

Semi-sacrificial fabrication of binder-free lithium-aluminum layered double hydroxides adsorbents for lithium extraction - Jinqiang Gao; Mei Hong; Jiatao Zhong; Shengnan Na; Yuqing Su; Han Li; Mingyu Hu; Shihe Yang (Desalination, 2025)

Considerable declines in odor in a drinking water reservoir: Variations of odorous community, precursor enzymes abundance, distribution, and environmental dominant factors - Honghong Guo; Rong Li; Shuhong Xue; Xuanzi Zhangsun; Daojun Huang; Yongchao Li; Na Li; Yuhang Su; Haihan Zhang; Tinglin Huang (Water Research, 2025)

ALFIN-like proteins link histone H3K4me3 to H2A ubiquitination and coordinate diverse chromatin modifications in Arabidopsis - Xiao-Min Su; Dan-Yang Yuan; Na Liu; Zhao-Chen Zhang; Minqi Yang; Lin Li; She Chen; Yue Zhou; Xin-Jian He (Molecular Plant, 2025)

Preparation and characterization of microcrystalline cellulose/corn starch-based active packaging enhanced by resveratrol/β-cyclodextrin complex - Na Yang; Haojie Sha; Wenlu Bi; Sheng Li; Shusong Wu; Dingding Su (Food Packaging and Shelf Life, 2025)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Abundance, characteristics and ecological risk assessment of microplastics in ship ballast water in ports around Liaodong Peninsula, China - Qing Su; Yuxia Li; Na Lu; Ling Qu; Xin Zhou; Yue Yu; Daping Lu; Junsong Han; Jianbo Han; Xiaotong Xu; Xiaomeng Wang (Marine Pollution Bulletin, 2024)

Selective and antibacterial zinc phosphonate framework system for superior marine uranium harvesting - Nan Li; Shideng Yuan; Ruidian Su; Jiakun Wu; Na Shi; Lei Wang; Zhining Wang (Desalination, 2024)

Magnesium hexacyanoferrate nanocatalysts alleviates fibromyalgia syndrome by reversing cellular ferroptosis - Ling Jiang; Zhongqiang Zhu; Kun Han; Dongxu Chen; Lu Huang; Na Hu; Jiayi Du; Bowen Zhang; Yi Su; Tao Li; Xiangyi Ren; Xiang He (Chemical Engineering Journal, 2024)

Chloride homeostasis via enhanced salt ion secretion selectivity contributes to salt tolerance of recretohalophytic mangrove Avicennia marina - Qian-Su Ding; Chao-Qun Xu; Dong-Na Ma; Ming-Yue Wei; Chang-Hao Gao; Shan Zhang; Huan Li; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2024)

Label-free SELEX of aptamers for ultra-sensitive electrochemical aptasensor detection of amanitin in wild mushrooms - Renxiang Yang; Changsong Zhao; Sheng Ding; Jia Ruan; Dongqiu Li; Yijia Xiang; Jie Zhou; Huilan Su; Na Li (Analytica Chimica Acta, 2024)

Resveratrol suppresses liver cancer progression by downregulating AKR1C3: targeting HCC with HSA nanomaterial as a carrier to enhance therapeutic efficacy - Ying Wang; Longxiang Su; Zhansheng Hu; Shuang Peng; Na Li; Haiyan Fu; Baoquan Wang; Huiping Wu (Apoptosis, 2024)

Immunotherapy shapes B-cell receptor repertoire to induce anti-tumor antibodies production in colon and lung cancer - Hang Su; Yimeng Wang; Sajid Khan; Yinan Huang; Zhenfei Yi; Na Zhu; Zhenghao Li; Feng Leng; Yanfen Chen; Lin Yang; Takaji Matsutani; Zhenghong Lin; et al. (Genome Instability & Disease, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

Towards Stem/Progenitor Cell-Based Therapies for Retinal Degeneration - Hui Liu; Shuaiyan Lu; Ming Chen; Na Gao; Yuhe Yang; Huijuan Hu; Qing Ren; Xiaoyu Liu; Hongxu Chen; Qunyan Zhu; Shasha Li; Jianzhong Su (Stem Cell Reviews and Reports, 2024)

Identification and molecular docking of a novel antidiabetic peptide from protamex-camel milk protein hydrolysates against α-amylase and DPP-IV - Na Su; Li Yi; Jing He; Liang Ming; Tuyatsetseg Jambal; Batmunkh Mijiddorj; B. Maizul; Ts. Enkhtuul; Rimutu Ji (International Dairy Journal, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Hydrogen production from steam reforming of biomass-derived levulinic acid over highly stable spinel-supported Ni catalysts - Tian Li; Hongcai Su; Lingjun Zhu; Dan Xu; Na Ji; Shurong Wang (Waste Disposal & Sustainable Energy, 2023)

Selective extraction of uranium from seawater on amidoximated MXene/metal-organic framework architecture under an electric field - Nan Li; Li Yang; Ruidian Su; Na Shi; Jiakun Wu; Jia Zhao; Liping Wen; Zhining Wang (Desalination, 2023)

Phase behavior tuning enable high-safety and crack-free Ni-rich layered cathode for lithium-ion battery - Na Liu; Lai Chen; Haoyu Wang; Jiayu Zhao; Fei Gao; Jing Liu; Jinyang Dong; Yun Lu; Ning Li; Qi Shi; Yuefeng Su; Feng Wu (Chemical Engineering Journal, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

Protein-rich yeast extract (®fermgard) has potential antioxidant and anti-aging activities - Quancen Li; Wenwen Cai; Na Li; Weibin Su; Haicheng Li; Haibo Zhang; Zhixian Chen; Shiyu Gong; Xiaodong Ge; Bin Liu; Feng Zeng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Ubiquitinomics revealed disease- and stage-specific patterns relevant for the 3PM approach in human sigmoid colon cancers - Hua Yang; Na Li; Liang Chen; Lei Zhou; Yuanchen Zhou; Jixiang Liu; Wenshuang Jia; Ruofei Chen; Junwen Su; Lamei Yang; Xiaoxia Gong; Xianquan Zhan (EPMA Journal, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

First report of Fusarium foetens causing root rot on lavender (Lavandula angustifolia) in China - Xue-Jun Wei; Bing-Guo Jia; Xing Wang; Nan-Yang Li; Su-Na Wang; Li Li; Ai Zhang; Hao-Tian Zhang; Li-Ping Wang (Journal of Plant Pathology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

RNAi-mediated knockdown of the mandibular organ-inhibiting hormone (MOIH) gene stimulates vitellogenesis in the Chinese mitten crab Eriocheir sinensis - Shuquan Ding; Mengting Huang; Na Sheng; Tiantian Chen; Ruihan Xu; Zhaoyuan Luo; Xiuqin Huang; Zhicheng Wan; Shiping Su; Xilei Li (Fisheries Science, 2023)

Global warming impact assessment of asphalt pavement by integrating temporal aspects: A dynamic life cycle assessment perspective - Dan Chong; Na Wang; Shu Su; Li Li (Transportation Research Part D: Transport and Environment, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Corolliform morphology thin film composite polyamide membrane constructed via Tröger's base PIM for enhancing nanofiltration separation performances - Tian-Hui Chen; Ting Su; Li Xia; Liu-Yang Gong; Bei-Na Dong; Li-Fen Liu (Desalination, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Methane supply drives prokaryotic community assembly and networks at cold seeps of the South China Sea - Mingyang Niu; Longhui Deng; Lei Su; S. Emil Ruff; Na Yang; Min Luo; Qi Qi; Jiangtao Li; Fengping Wang (Molecular Ecology, 2023)
Marine cold seeps are unique chemosynthetic habitats fuelled by deeply sourced hydrocarbon‐rich fluids discharged at the seafloor. Through oxidizing methane and other hydrocarbons, microorganisms inhabiting cold seeps supply subsurface‐derived energy to higher trophic levels, sustaining highly productive oases of life in the deep sea. Despite the central role of microbiota in mediating biogeochemical cycles, the factors that govern the assembly and network of prokaryotic communities in cold seeps remain poorly understood. Here we analysed the geochemical and microbiological profiles of 11 different sediment cores from two spatially distant cold seeps of the South China Sea. We show that prokaryotic communities belonging to the same methane‐supply regimes (high‐methane‐supply, low‐methane‐supply and non‐seep control sediments) had a highly similar community structure, regardless of geographical location, seep‐associated biota (mussel, clam, microbial mat) and sediment depth. Methane supply appeared to drive the niche partitioning of anaerobic methanotrophic archaea (ANME) at the regional scale, with ANME‐1 accounting for >60% sequence abundance of ANME in the high‐methane‐supply sediments, while ANME‐2 dominated (>90%) the low‐methane‐supply sediments. Increasing methane supply enhanced the contribution of environmental selection but lessened the contributions of dispersal limitation and drift to overall community assembly. High methane supply, moreover, promoted a more tightly connected, less stable prokaryotic network dominated by positive correlations. Together, these results provide a potentially new framework for understanding the niches and network interplay of prokaryotic communities across different methane seepage regimes in cold‐seep sediments.

Multimedia fates and ecological risk control strategies of phthalic acid esters in a lake recharged by reclaimed water using the QWASI fugacity model - Chenchen Wang; Jing Li; Chunsheng Qiu; Lei Wang; Xiao Su; Panpan Huang; Na He; Liping Sun; Yaohui Bai; Chaocan Li; Yufei Wang (Ecological Modelling, 2023)

Bioinspired green tea waste/graphene aerogel for solar-enhanced uranium extraction from seawater - Nan Li; Jiakun Wu; Ruidian Su; Na Zhang; Jia Zhao; Zhining Wang (Desalination, 2023)

The growth and lipid accumulation of Scenedesmus quadricauda under nitrogen starvation stress during xylose mixotrophic/heterotrophic cultivation - Yiwen Mou; Na Liu; Kunyang Su; Xue Li; Tianxiang Lu; Ze Yu; Mingming Song (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Cloning and expression analysis of juvenile hormone epoxide hydrolase-like ( EsJHEH-like ) from Eriocheir sinensis , and its potential roles in methyl farnesoate metabolism - Tiantian Chen; Yingzhu Diao; Ruihan Xu; Na Sheng; Fan Liu; Qiming Xie; Shiping Su; Keyi Ma; Xilei Li (Invertebrate Reproduction & Development, 2022)

Circ_0001666 affects miR-620/WNK2 axis to inhibit breast cancer progression - Na Su; Li Liu; Shan He; Linghai Zeng (Genes & Genomics, 2021)

Divalent tranylcypromine derivative as lysine-specific demethylase 1 inhibitor - Yin Sun; Na Li; Mingbo Su; Xiaowen Wang; Dongmei Zhao; Bing Xiong; Yubo Zhou; Tongchao Liu; Yue-Lei Chen (Medicinal Chemistry Research, 2021)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Prenatal diagnosis of 22q11.2 copy number abnormalities in fetuses via single nucleotide polymorphism array - Meiying Cai; Na Lin; Linjuan Su; Xiaoqing Wu; Xiaorui Xie; Ying Li; Yuan Lin; Hailong Huang; Liangpu Xu (Molecular Biology Reports, 2020)
The q11.2 region on chromosome 22 contains numerous low-copy repeats that lead to deleted or duplicated regions in the chromosome, thereby resulting in different syndromes characterized by intellectual disabilities or congenital anomalies. The association between patient phenotypes and 22q11.2 copy number abnormalities has been previously described in postnatal cases; however, these features have not been systematically evaluated in prenatal cases because of limitations in phenotypic identification in prenatal testing. In this study, we investigated the detection rate of 22q11.2 copy number abnormalities in 2500 fetuses using single nucleotide polymorphism (SNP) array and determined the common abnormal ultrasound findings in fetuses carrying the 22q11.2 copy number abnormalities. The 22q11.2 copy number abnormalities were identified in 13 fetuses with cardiovascular malformations (6/13), kidney malformations (3/13), isolated ultrasound markers (3/13), or high-risk Down syndrome based on maternal serum screening (1/13). Approximately 0.5% (13/2500) of the fetuses harbored 22q11.2 copy number abnormalities. The most frequent ultrasound findings in fetuses with these abnormalities were cardiovascular malformations, followed by kidney malformations and isolated ultrasound markers. Prenatal diagnosis of these genetic abnormalities allows for the delineation of differential diagnoses, characterization of a wide spectrum of associated malformations, and determination of associations that exist between prenatal diagnosis and obstetrical outcomes.

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Genome-wide identification, phylogeny, and expression analysis of Sec14-like PITP gene family in sugarcane - Mao Hua-ying; Wang Wen-ju; Su Wei-hua; Su Ya-chun; Liu Feng; Li Cong-na; Wang Ling; Zhang Xu; Xu Li-ping; Que You-xiong (Plant Cell Reports, 2019)

Sulfide Rb-Sr and Zircon U-Pb Dating of the ~825 Ma Liujiaping Cu-Zn deposit in the Northwestern Yangtze Block (China) and its tectonic implications - Yan-Ping Su; Bao-Lin Zhang; Hui-Zhong Li; Ya-Na Miao; Xiao-Li Shen (International Geology Review, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Ascorbic acid inhibits cadmium-induced disruption of the blood-testis barrier by regulating oxidative stress-mediated p38 MAPK pathways - Na Chen; Ping Su; Mei Wang; Ya-Min Li (Environmental Science and Pollution Research, 2018)

Physical Stability of Amorphous Solid Dispersions: a Physicochemical Perspective with Thermodynamic, Kinetic and Environmental Aspects - Xia Lin; Yang Hu; Lei Liu; Lili Su; Na Li; Jing Yu; Bo Tang; Ziyi Yang (Pharmaceutical Research, 2018)

Development of a reverse transcription recombinase-aided amplification assay for the detection of coxsackievirus A10 and coxsackievirus A6 RNA - Teng-fei Yan; Xin-na Li; Le Wang; Chen Chen; Su-xia Duan; Ju-ju Qi; Li-Xin Li; Xue-jun Ma (Archives of Virology, 2018)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

Effect of Partial Shading Treatments on Anthocyanin Synthesis in the Hypocotyls of Soybean Sprouts Under UV-A irradiation - Nana Su; Qi Wu; Nannan Qi; Yuanyuan Liu; Na Li; Jin Cui (Journal of Plant Growth Regulation, 2017)

Snowfall-related deterioration behavior of the Ming Great Wall in the eastern Qinghai-Tibet Plateau - Tianbiao Pu; Wenwu Chen; Yumin Du; Wenjuan Li; Na Su (Natural Hazards, 2016)

Therapeutic effects of histone deacetylase inhibitors in a murine asthma model - Yuan Ren; Xinming Su; Lingfei Kong; Menglu Li; Xuan Zhao; Na Yu; Jian Kang (Inflammation Research, 2016)

Transcriptomic analysis reveals key early events of narciclasine signaling in Arabidopsis root apex - Xiaoning Cao; Fei Ma; Tingting Xu; Junjie Wang; Sichen Liu; Gaihong Li; Qian Su; Zhijun Qiao; XiaoFan Na (Plant Cell Reports, 2016)

Melatonin attenuates angiotensin II-induced cardiomyocyte hypertrophy through the CyPA/CD147 signaling pathway - Hongyan Su; Jingyuan Li; Tongshuai Chen; Na Li; Jie Xiao; Shujian Wang; Xiaobin Guo; Yi Yang; Peili Bu (Molecular and Cellular Biochemistry, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Myricetin protects against diet-induced obesity and ameliorates oxidative stress in C57BL/6 mice - Hong-ming Su; Li-na Feng; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

An Ime2-like mitogen-activated protein kinase is involved in cellulase expression in the filamentous fungus Trichoderma reesei - Fei Chen; Xiu-Zhen Chen; Xiao-Yun Su; Li-Na Qin; Zhen-Bang Huang; Yong Tao; Zhi-Yang Dong (Biotechnology Letters, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Quantitative trait loci mapping of partial resistance to Diamondback moth in cabbage (Brassica oleracea L) - Nirala Ramchiary; Wenxing Pang; Van Dan Nguyen; Xiaonan Li; Su Ryun Choi; Ajay Kumar; Min Kwon; Hye Young Song; Shahnaz Begum; Mechuselie Kehie; Moo-Kyoung Yoon; Jonghyun Na; et al. (Theoretical and Applied Genetics, 2015)

Impacts of Transportation Routes on Landscape Diversity: A Comparison of Different Route Types and Their Combined Effects - Shiliang Su; Rui Xiao; Delong Li; Yi’na Hu (Environmental Management, 2014)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

The respiratory burst activity and expression of catalase in white shrimp, Litopenaeus vannamei, during long-term exposure to pH stress - Wei-Na Wang; Bao-Sheng Li; Jin-Jian Liu; Lei Shi; M. J. Alam; Shi-Juan Su; Juan Wu; Lei Wang; An-Li Wang (Ecotoxicology, 2012)

Down-regulation of β3-integrin inhibits bone metastasis of small cell lung cancer - Na Li; Jian-ping Zhang; Shan Guo; Jie Min; Li–li Liu; Hai-chuan Su; Ying-ming Feng; He-long Zhang (Molecular Biology Reports, 2012)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

Isolation and characterization of an AHL lactonase gene from Bacillus amyloliquefaciens - Xiang-Tian Yin; Liang Xu; Su-Su Fan; Li-Na Xu; Duo-Chuan Li; Zhen-Yu Liu (World Journal of Microbiology and Biotechnology, 2010)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Spatial distribution of Cd and Cu in soils in Shenyang Zhangshi Irrigation Area (SZIA), China - Li-na Sun; Xiao-bo Yang; Wen-qing Wang; Li Ma; Su Chen (Journal of Zhejiang University-SCIENCE B, 2008)